Analisis Swasembada Pangan di Tingkat Desa Melalui Pendekatan Partisipatif (Studi Kasus pada Badan Usaha Milik Gampong (BUMG) di Gampong Blang Aceh Indonesia) - Elliza Elliza; Taufiq Taufiq; Muslina Muslina (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
This study aims to analyze the role of the Village-Owned Enterprise (BUMG) of Gampong Blang in strengthening community food security through the agriculture and plantation management program. To delineate the impacts of BUMG program implementation on enhancing economic access, promoting sustainable utilization of local resources, and improving the welfare of beneficiary communities to foster the long-term sustainability of community-based food security. Primary data sources include interviews with the village head, all BUMG managers, and thirty community members who are beneficiaries of the program. Additionally, observations and documentation serve as supporting data for the interviews, which are subsequently analyzed using a descriptive qualitative approach. The results show the role and impact of BUMG in enhancing food security for the community of Gampong Blang from several aspects: (1) The Gampong Blang BUMG in Aceh has successfully created 12,800 hectares of rice fields with a total of 16 farmers receiving benefits in 2023, who must pay 300 thousand, while the garden land produces chilies, cucumbers, papayas, and vegetables from 1,600 meters of land with a turnover of 12 million in 2023. (3) According to the theoretical review of Community-Based Food Security, BUMG is a key actor in realizing community participation, smooth economic access, and utilization of local resources to ensure the sustainability of food programs. (3) Managing profits from the BUMG program to improve community welfare in various areas, including education, consumption expenses, business capital, home renovations, and health sector incentives. All of these initiatives stem from developing the region's potential, starting with enhancing competencies.